At-Tamyīz al-ʿIrqī Ḍidda al-Filasṭīniyyīn fī Fīlm 200 Metr li-Amīn Nāyifah (Dirāsah fī ʿIlm al-Adab al-Ijtimāʿī) - Amrullah, Riki; Yusuf, Muhammad; Muttaki, Muttaki (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
This article is derived from an undergraduate thesis entitled At-Tamyīz al-ʿIrqī Ḍidda al-Filasṭīniyyīn fī Fīlm 200 Metr li-Amīn Nāyifah. The study aims to analyze forms of racial discrimination against Palestinians as represented in the film 200 Meter using the sociology of literature approach proposed by Alan Swingewood and supported by discrimination theory formulated by Fulthoni et al. This research employs a qualitative descriptive method with a library research design. The primary data source is the film 200 Meter, while secondary data include books, academic journals, and relevant reports. The findings reveal four main forms of discrimination: permit and labor discrimination, smuggling practices, discriminatory treatment at checkpoints and vehicles with Israeli license plates, and discrimination among Palestinians themselves. Furthermore, the film reflects social realities experienced by Palestinians, such as restrictions on movement, labor dependency, identity fragmentation, and systemic control. The study concludes that 200 Meter functions as a socio-literary reflection that critically represents Palestinian lived experiences under structural discrimination.